RANCANG BANGUN PEMBANGKIT EBT DENGAN PEMANFAATAN SOLAR PV ON GRID SYSTEM BERBASIS ARDUINO MEGA 2560 - Muhammad Halim Sa’id; Unggul Wibawa; Teguh Utomo (Jurnal Mahasiswa TEUB, 2023)
Indonesia has saved 4.8 kWh/m2 or the equivalent of 112,000 GWp. This potential is the biggest when compared to the five existing types of EBT sources. However, the utilization is only a little, namely 0.08% or the equivalent of only 10 MWp. . The purpose of this study is to determine the effect of the EBT by utilizing the Arduino Mega 2560 based Solar PV On Grid System in the supply of electrical energy in the UT School Building. There are two software needed in this study which include: Arduino IDEand Nextion Editor. Based on the average test results using the RMSD measurement method which was carried out from 13 December 2022 to 28 December 2022, it was found that the potential of a 1050 Wp solar panel monitored by HMI Nextion in the UT School building produced 0.68 A and 112.69 V in the sunlight intensity 195.71 W/m2 and temperature 26.93oC. From this, it can be seen that the contribution of electrical energy generated by the on-grid EBT system monitored by the Arduino Mega 2560 is 7.33% of the total electrical energy of the UT School building. Index Terms— Solar Panel, Arduino Mega 2560, RMSD.